Palladium-catalyzed asymmetric hydrophosphorylation of alkynes: facile access to P-stereogenic phosphinates. Issue 28 (7th July 2020) - Yang, Zhiping; Gu, Xiaodong; Han, Li-Biao; Wang, Jun (Joelle)
Abstract : A catalytic enantioselective synthesis of P -stereogenic alkenylphosphinates is developed through asymmetric hydrophosphorylation. This process is demonstrated on racemic phosphinates and leads to diverse P -stereogenic alkenylphosphinates directly. Abstract : Despite the importance of P -chiral organophosphorus compounds in asymmetric catalysis, transition metal-catalyzed methods for accessing P -chiral phosphine derivatives are still limited. Herein, a catalytic enantioselective method for the synthesis of P -stereogenic alkenylphosphinates is developed through asymmetric hydrophosphorylation of alkynes. This process is demonstrated for a wide range of racemic phosphinates and leads to diverse P -stereogenic alkenylphosphinates directly.